Kontribusi Pengalaman Kerja dan Motivasi Kerja terhadap Profesionalisme Guru Pembimbing di SMA Se-Kabupaten Tabanan - Ni Putu Seniwati; Ni Made Rai Wisudariani; I Wayan Nayun (Universitas Mathla'ul Anwar Banten, 2021)
THE CONTRIBUTION OF WORK EXPERIENCE AND WORK MOTIVATION TO THE PROFESSIONALISM OF SUPERVISING TEACHERS IN HIGH SCHOOLS IN TABANAN REGENCY. This study focused on the study of the contribution of work experience and work motivation to the professionalism of supervising teachers in Senior High Schools in Tabanan Regency. This study used an ex post facto design involving 39 respondents from 14 Public and Private Senior High Schools in Tabanan Regency. Data were obtained through documentation method and questionnaires which were analyzed by regression analysis. The results showed that there was a significant contribution between work experience and the professionalism of the supervisor, and there was a significant contribution between work motivation and the professionalism of the supervisors.